Christopher Southgate on Glory and Compassion - Sollereder, Bethany N. (Theology and science, 2019)
This article was presented at the 2018 American Academy of Religion conference at a panel honouring the work of Christopher Southgate. The first half is a response to the theology of glory in Southgate's Theology in a Suffering World (CUP 2018). The second half expands on Southgate's work on practical theodicy. I argue for a redirection of the work of theodicy toward a compassionate approach, outlined by three principles that are centred around helping those who suffer create their own theodicies. The job of the practical and compassionate theodicist, then, is not to provide answers for why suffering occurs, but rather to offer resources to help others frame their own experience.